2017
DOI: 10.1371/journal.pone.0169868
|View full text |Cite
|
Sign up to set email alerts
|

Uniquely altered transcripts are associated with immune preservation in HIV infection

Abstract: The mechanisms underlying host HIV control hold much promise in the search for a functional HIV cure. We investigated the host genomic signatures in elite controllers or rapid progressors following recent infection and the correlates of immune reconstitution during combination antiretroviral therapy. We characterized the HIV-specific longitudinal host transcriptional response of peripheral blood mononuclear cells from elite controllers, rapid progressors, immune responders and non-responders using a RT-qPCR ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…Biological pathways for RNA-seq data are depicted in Supplementary Table 7 Some of the up-regulated genes were Interleukin-6 (IL-6) and Interleukin-1 beta (IL-1β), two well known pro-inflammatory mediators 26 , 27 , and also Interleukin-10. Previous reports demonstrated that the natural suppression of HIV was associated with the highly functional co-expression of cytokines such as TNF and IL-10 concomitant with significant maintenance of anti-inflammatory and anticoagulant properties 28 .
Figure 5 Gene expression analysis.
…”
Section: Resultsmentioning
confidence: 99%
“…Biological pathways for RNA-seq data are depicted in Supplementary Table 7 Some of the up-regulated genes were Interleukin-6 (IL-6) and Interleukin-1 beta (IL-1β), two well known pro-inflammatory mediators 26 , 27 , and also Interleukin-10. Previous reports demonstrated that the natural suppression of HIV was associated with the highly functional co-expression of cytokines such as TNF and IL-10 concomitant with significant maintenance of anti-inflammatory and anticoagulant properties 28 .
Figure 5 Gene expression analysis.
…”
Section: Resultsmentioning
confidence: 99%